Dynamics of changes in the morphometric dimensions of the free wing bones in Japanese Quails - Abdullaeva Dilbar; Dilmuradov Nasriddin; Khudaynazarova Nilufar; Doniyorov Shohruh; Mukhtarov Elmurod (BIO Web of Conferences)
The study examines the dynamics of changes in the morphometric dimensions of the free wing bones in Japanese quails that received and did not receive probiotics during postnatal ontogenesis. It was noted that the absolute indicators of the morphometric parameters of the humerus, radius, and ulna in quails that did not receive probiotics increased sharply until the 25th day of postnatal ontogenesis, stabilized between 25 and 60 days of age, and slowed down after the 120th day due to egg-laying levels. In quails that received probiotics, the intensive stage of increasing the absolute indicators of the morphometric dimensions of the humerus, radius, and ulna occurred earlier — already by the 15th day of postnatal ontogenesis — compared to quails that did not receive probiotics. During the period from day 1 to day 294 of postnatal ontogenesis, the growth dynamics of the morphometric parameters of the humerus, radius, and ulna were found to be significantly higher in Japanese quails administered probiotics compared to those without probiotic supplementation. Additionally, in both probiotic-treated and untreated quails, the growth coefficient of these bones was significantly higher in terms of mass than in terms of length.